2019
DOI: 10.26650/iuitfd.391192
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels in Routine Medical Examination

Abstract: Med -Available online at jmed.istanbul.edu.tr ©Telif Hakkı 2018 J Ist Faculty Med -Makale metnine jmed.istanbul.edu.tr web sayfasından ulaşılabilir.ÖZET Amaç: D vitamini eksikliği dünya genelindeki gibi Türkiye'de de önemli halk sağlığı sorunlarındandır ve literatürde özellikle yaşlı popülasyonda osteoporoz, düşme riski ve kırıklar gibi birçok morbidite ile ilişkili olduğunu gösteren veriler mevcuttur. Gereç ve Yöntem: 2013-2016 yılları arasında rutin sağlık taraması amacıyla Istanbul Medicine Hospital'e başvu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Certain changes in 25(OH)D metabolism occur as individuals age, including a reduction in vitamin D receptor levels, renal 1.25(OH)2D synthesis, and cutaneous 25(OH)D production [24]. Çağlayan et al [25] and Şenyiğit et al [26] have corroborated these findings, confirming a decline in 25(OH)D levels with increasing age. In our study, we identified a weak negative correlation between age and 25(OH)D levels.…”
Section: Discussionmentioning
confidence: 89%
“…Certain changes in 25(OH)D metabolism occur as individuals age, including a reduction in vitamin D receptor levels, renal 1.25(OH)2D synthesis, and cutaneous 25(OH)D production [24]. Çağlayan et al [25] and Şenyiğit et al [26] have corroborated these findings, confirming a decline in 25(OH)D levels with increasing age. In our study, we identified a weak negative correlation between age and 25(OH)D levels.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, Slinin et al (30) associated lower 25-OHD levels with a higher likelihood of cognitive impairment and decline among older women. In a study of 688 patients in Turkey, Senyigit et al (31) found that older women had lower 25-OHD levels.…”
Section: One Of the Most Comprehensive Studies Of Vitamin D Status In...mentioning
confidence: 99%
“…Osteoporosis is one of the most threatening conditions in the older population with the progression of age; the most important factor that causes osteoporosis is vitamin D deficiency [55,56]. Vitamin D is essential for calcium metabolism and bone quality [38,57,58].…”
Section: Vitamin D Deficiency and Health-promoting Practicesmentioning
confidence: 99%
“…Although there is plenty of sunlight in Turkey, insufficient exposure to sunlight and wearing plenty of clothing due to sociocultural/religious beliefs are factors leading to vitamin D deficiency in the elderly [57]. Routine health-promoting practices in this group in Turkey are focused in education and counseling [56]. Recommendations are made to encourage the consumption of seafood, milk and dairy products, to supplement vitamin D and Calcium, and to increase the exposure to sunlight during the day [56,60].…”
Section: Vitamin D Deficiency and Health-promoting Practicesmentioning
confidence: 99%
See 1 more Smart Citation